The NH Functional Group in Organometallic Catalysis - Zhao, Baoguo; Han, Zhaobin; Ding, Kuiling (Angewandte Chemie International Edition, 2013)
The organometallic approach is one of the most active topics in catalysis. The application of NH functionality in organometallic catalysis has become an important and attractive concept in catalyst design. NH moieties in the modifiers of organometallic catalysts have been shown to have various beneficial functions in catalysis by molecular recognition through hydrogen bonding to give catalyst–substrate, ligand–ligand, ligand–catalyst, and catalyst–catalyst interactions. This Review summarizes recent progress in the development of the organometallic catalysts based on the concept of cooperative catalysis by focusing on the NH moiety. The “magic” effects of NH moieties in organometallic catalysis have been observed in various reaction systems. Recent advances are presented in the development of organometallic catalysts based on the concept of cooperative catalysis by taking the beneficial effect of the NH moiety in the catalyst by catalyst–substrate, ligand–ligand, and catalyst–catalyst interactions.